(untitled) (Journal of Dhaka Medical College, 2017)
The pathogenesis of gentamicin-induced nephrotoxicity has shown to generate oxygen free radicals. Several free radical scavengers are well recognized to ameliorate the nephrotoxicity. The seeds and oil of nigella sativa were reported to possess strong antioxidant properties and was effective against disease and chemically-induced hepatotoxicity and nephrotoxicity.The experiments were carried out in two parts, Experiment I and Experiment II, on a total of 35 rats of 8-12 weeks old and weighing between 200 and 230g. Nephrotoxicity and amelioration of nephrotoxicity was evaluated by measurement of concentrations of serum creatinine. The rats were induced nephrotoxicity by subcutaneous injection of gentamicin 100mg/kg/day for 9 days and were sacrificed on 10th day. The results indicated that gentamicin treatment caused marked renal tubular damage significant increase (P<0.001) of serum creatinine concentrations when compared to those of control.When n-hexane extract of N.sativa was administered as low and high dose with gentamicin and compared with the gentamicin treated groups, it was found that in these two groups there was significant decrease (P<0.001) of serum creatinine levels. When these two groups were compared with each other, it was observed that more amelioration occurred significantly in high dose treatment group than in the low dose treatment group. This study established that oral administration of n-hexane extract of N. sativa was able to produce considerable improvement from the nephrotoxic action of gentamicin in rats. The best amelioration was obtained in high dose treatment. Low dose treatment brought out the least amelioration of them all. Future works could better be directed towards obtaining the specific ingredient and the specific mechanism responsible for nephroprotection. We are hopeful that complete amelioration might not be impossible if given in proper doses or more effectively if we could extract the actual ingredients responsible for nephroprotection and can use them eventually. J Dhaka Medical College, Vol. 25, No.2, October, 2016, Page 119-123